Algorithmic Anthropomorphizing, Platform Gossip, and Backlashes: Aspirational Content Creators’ Narratives About YouTube’s Algorithm on Reddit - John R. Gallagher; Antonia Pecoraro Hernandez (Social Media + Society)
This paper examines how aspirational content creators (ACCs) on the r/NewTubers subreddit forum understand and discuss YouTube’s algorithm. This study employs thematic analysis of 144 r/NewTubers posts that explicitly mentioned algorithms. The analysis reveals four main themes: mythologizing and anthropomorphism, demystification of the algorithm, platform gossip, and community backlash. NewTubers often personify the algorithm, attributing human-like qualities and agency to it. This anthropomorphism, however, is frequently challenged by other NewTubers who emphasize the algorithm’s technical nature and the importance of content quality. These narratives highlight the formation of public, non-institutional algorithmic literacies among ACCs as they negotiate the opaque world of platform algorithms.